Perancangan Sistem Informasi Monitoring Data KWH Meter Menggunakan Metode User Centered Design (UCD) - Muhammad Afif Nafidz; Muhamad Kadafi (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The management of kWh meter replacement data at PLN ULP Ampera Palembang is still largely handled through manual recording, which often causes data inconsistencies and delays in monitoring activities. This study aims to design an information system that supports the monitoring of kWh meter replacement data based on actual user needs. The research applies a descriptive qualitative method using the User Centered Design (UCD) approach, where users are actively involved throughout the design process. The stages include understanding the work context, identifying user requirements, developing system design solutions, and evaluating the proposed design. The outcome of this research is a kWh meter data monitoring system design that is expected to facilitate data management, improve accuracy, and support more efficient monitoring processes.